LIVE Course for free

Rated by 1 million+ students
Get app now
0 votes
16 views
in Aptitude by (54.3k points)
closed by
Find (x - 3)3+ (x + 3)3 + (- 2x)3
1. x + 5x3
2. -6x+ 54x
3. 2x3 + 54
4. 6x3 + 7

1 Answer

0 votes
by (30.0k points)
selected by
 
Best answer
Correct Answer - Option 2 : -6x+ 54x

Given:

(x - 3)3+ (x + 3)3 + (- 2x)3

Concept

If a + b + c = 0, then a+ b+ c= 3abc

(a - b)(a + b) = a2 - b2

Calculation

a = (x - 3), b = (x + 3) and c = -2x

⇒ 3 × (x - 3) × (x + 3) × (-2x)

⇒ 3 × (x2 - 9) × (-2x)

⇒ 3 × (-2x3 + 18x)

⇒ -6x3 + 54x

∴ (x - 3)+ (x + 3)3 + (-2x)3 is -6x3 + 54x.

No related questions found

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...